The Effect of Google Classroom Media on Responsibility Characters in SMKN 3 Jombang - Diah Puji Nali Brata; Eva Fitria Veranda (STAI Miftahul Ula Nganjuk, 2025)
Education has a role in forming quality and quality human resources. The role of the teacher as a component of learning must have creativity in creating learning media so that the learning process is effective. Increasing the effectiveness of the learning process shows the achievement of learning objectives. Most Civics teachers still use the lecture method so that students only master knowledge. Students need meaningful learning to develop aspects of knowledge, skills, and attitudes. One of the media that can be used to strengthen the learning experience of students is the Google Classroom media designed to help teachers create, describe and distribute assignments to students in a paperless manner (without paper). The Google Classroom application can also foster character, one of which is the responsibility of students. The purpose of this study was to reveal the influence of Google Classroom media on the character of responsibility in SMK N 3 Jombang. The method used in this research is quantitative, data collection in this study using a questionnaire. The results of this study can be concluded that from testing using SPSS version 21 shows the value of r count 0.060> r table 0.312 with a significant 0.713 <0.05, so it shows that there is an effect of Google Classroom learning media on the responsibility of students.